Complete plastid genome sequence of a medical herb, Anisomeles indica (L.) Kuntze (Lamiaceae). Issue 2 (3rd July 2019) - Yao, Gang; Huang, Jiuxiang; Li, Yuling
Abstract: The species Anisomeles indica is used medicinally and widely distributed from India, to China and the Indo-China Peninsula. The first complete plastid genome sequence of A. indica reported here was 151, 900 bp long, with the large single copy (LSC) region of 83, 144 bp, the small single copy (SSC) region of 17, 556 bp and two inverted repeats (IRa and IRb) of 25, 600 bp. The plastome contained 113 genes, including 79 protein-coding genes, 4 ribosomla RNA genes and 30 transfer RNA genes. The overall GC content was 38.26%. Result from phylogenetic analysis suggests that Anisomeles is closely related to the genus Pogostemon .